Young, Depressed, and Black: A Comparative Exploration of Depressive Symptomatology Among Black and White Collegiate Women. Issue 1 (2nd January 2018) - Longmire-Avital, Buffie; Robinson, Ruthie
ABSTRACT: This comparative study explored the rates of depression and psychosocial correlates for 369 collegiate White and Black females. Women between the ages of 18 and 25 were recruited to participate in this anonymous online survey. Black females reported significantly greater amounts of depressive symptomatology ( M  = 24.61) in comparison to the White females ( M  = 15.68), ( F (1, 377) = 61.434, p  < .001). A series of Chi-square analyses indicated that Black women (52.3%) were also significantly more likely to meet criteria for major depression than White women (21.7%). These findings highlight the racial disparities in psychosocial health among college students.